Use of acupuncture in depression - Santos, Elem Guimaraes dos (2021)
This is a descriptive, quantitative and cross-sectional study carried out from January to March 2020, in Vitória, ES, Brazil. It aims to describe the effects of acupuncture on adults with depression in a psychiatric institution. Data collection used a form containing sociodemographic information, acupuncture assessment form and the Hamilton Scale. Among the twenty subjects evaluated, a comparison was made among eight subjects, of which four from the intervention group (with the application of 10 sessions with a maximum of 10 points) and four from the control group (without the application of acupuncture). The results showed that there was improvement in the signs and symptoms associated with depression, with a reduction in the Hamilton scale score from 21.75 to 8.0 in the patients who received treatment with acupuncture; that is, from the condition of severe depression to mild depression. In addition, patients mentioned improvement in their sleep, mood, libido, control of emotions, relaxation and decreased pain. Acupuncture has shown beneficial effects in patients with depression.